2016
DOI: 10.1101/sqb.2016.81.030841
|View full text |Cite
|
Sign up to set email alerts
|

To Prime, or Not to Prime: That Is the Question

Abstract: Mitochondrial priming is regulated by the B-cell lymphoma 2 (BCL-2) family of proteins and determines a cell's "readiness" for apoptosis. A highly primed cell will undergo apoptosis more easily than an unprimed cell in response to apoptotic stimuli via the intrinsic apoptotic pathway. Priming can be measured via BH3 profiling, which uses BH3 peptides derived from the BH3 domain of pro-apoptotic BH3-only BCL-2 family members to provoke a response from viable mitochondria. BH3 profiling can be performed on tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 77 publications
0
49
0
Order By: Relevance
“…In our cartilage explant system, navitoclax showed consistent and robust elimination of the p16 tdTom ‐positive chondrocyte population with a single treatment for 3 d. The observation that the fluorescence intensity of the p16 tdTom ‐negative fraction was unchanged, combined with the initiation of cleaved caspase‐3 after navitoclax treatment, suggests that down‐regulation of p16 Ink4a expression was not responsible but that selective apoptosis was the primary mechanism for this result. Because of the complex regulation of apoptosis by the Bcl‐2 family of proteins, experimental approaches such as BH3 profiling (57) may be required to determine the precise mechanisms by which p16‐high chondrocytes are preferentially targeted for cell death upon navitoclax treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In our cartilage explant system, navitoclax showed consistent and robust elimination of the p16 tdTom ‐positive chondrocyte population with a single treatment for 3 d. The observation that the fluorescence intensity of the p16 tdTom ‐negative fraction was unchanged, combined with the initiation of cleaved caspase‐3 after navitoclax treatment, suggests that down‐regulation of p16 Ink4a expression was not responsible but that selective apoptosis was the primary mechanism for this result. Because of the complex regulation of apoptosis by the Bcl‐2 family of proteins, experimental approaches such as BH3 profiling (57) may be required to determine the precise mechanisms by which p16‐high chondrocytes are preferentially targeted for cell death upon navitoclax treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Using luciferase reporter assays and ChIP analysis, it was shown that c‐Myc directly binds to the FLIP promoter to effect this change . A recent paper from the Letai lab proposed that highly proliferative tissues with high c‐Myc activity (as is found in many cancers) are apoptotically primed; in this regard, c‐Myc‐mediated repression of FLIP expression may contribute to this apoptotic priming . In conclusion, FLIP is regulated by multiple, interconnected pathways providing potential opportunities for indirect modulation of FLIP by agents targeting the relevant pathways in specific tissues/cancers ( see below ).…”
Section: Flip Regulationmentioning
confidence: 99%
“…Currently, BH3-profiling is the technique used to assay the state of apoptotic 752 priming for different tissue types, however, this technique requires the addition of BH3 753 peptides at high concentrations, and can only be performed on cells/tissues after 754 permeabilization of the plasma membrane (Potter and Letai 2016). As an alternative, we 755…”
mentioning
confidence: 99%